2013
DOI: 10.1016/j.bbrc.2012.11.071
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK alpha mediates cytokine-induced IL-6 and MMP-3 expression in human cardiac fibroblasts

Abstract: Highlights► The p38 MAPK signaling pathway regulates cardiac remodeling. ► Human cardiac fibroblasts express the α, γ and δ subtypes of p38 MAPK. ► IL-1 selectively stimulates p38α and p38γ activation. ► p38α is important for IL-1-induced IL-6 and MMP-3 expression in cardiac fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 34 publications
(31 reference statements)
1
52
1
Order By: Relevance
“…The remodeling heart is characterized by increased levels of various proinflammatory cytokines, such as interleukin (IL)-1, IL-6 and tumor necrosis factor α (TNFα) (Nicoletti and Michel, 1999;Porter and Turner, 2009;Souders et al, 2009). CF actively contribute to this inflammatory milieu by secreting various cytokines and chemokines, which attract and activate immune cells (Sinfield et al, 2013;Turner et al, 2011;Turner et al, 2009;Turner et al, 2010). On the other hand, elevated levels of anti-inflammatory factors such as transforming growth factor β1 (TGFβ1), derived from both infiltrating immune cells and myocardial cells, reduce inflammation and lead to differentiation of CF to myofibroblasts (CMF) (Leask, 2010;Lijnen et al, 2000;van den Borne et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remodeling heart is characterized by increased levels of various proinflammatory cytokines, such as interleukin (IL)-1, IL-6 and tumor necrosis factor α (TNFα) (Nicoletti and Michel, 1999;Porter and Turner, 2009;Souders et al, 2009). CF actively contribute to this inflammatory milieu by secreting various cytokines and chemokines, which attract and activate immune cells (Sinfield et al, 2013;Turner et al, 2011;Turner et al, 2009;Turner et al, 2010). On the other hand, elevated levels of anti-inflammatory factors such as transforming growth factor β1 (TGFβ1), derived from both infiltrating immune cells and myocardial cells, reduce inflammation and lead to differentiation of CF to myofibroblasts (CMF) (Leask, 2010;Lijnen et al, 2000;van den Borne et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, IL-1α induced metalloproteinases MMP1, MMP3, MMP9 and MMP10 (Sinfield et al, 2013;Turner et al, 2010); indicating that increased levels of this cytokine have important consequences for ECM degradation. Increased MMP expression and activity was also observed in rat CF stimulated by IL-1β (Brown et al, 2007) or TNFα (Siwik et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CF may contribute to the inflammatory milieu that occurs in the myocardium early after MI [10,95]. In addition to this inflammatory response, we [7,88,93,94,[96][97][98] and others [61,99,100] have demonstrated that CF alter the balance of cardiac ECM turnover in favour of degradation in response to IL-1; for example by increasing secretion of MMPs, decreasing collagen synthesis and decreasing expression of profibrotic factors (e.g. connective tissue growth factor).…”
Section: Interleukin-1mentioning
confidence: 78%
“…IL-1 , IL-6, TNF-) and neutrophilattracting chemokines (e.g. CXCL-1, 2, 5 and 8), and express specific neutrophil-binding adhesion molecules including ICAM-1 and E-selectin [88,[90][91][92][93], as well as the matricellular protein TN-C [94]. Thus, CF may contribute to the inflammatory milieu that occurs in the myocardium early after MI [10,95].…”
Section: Interleukin-1mentioning
confidence: 99%
“…We therefore investigated the role of individual p38 MAPK subtypes in mediating IL-1-induced IL-6 and MMP-3 gene expression in human CF (Sinfield et al, 2013). Quantitative RT-PCR and Western blotting of cells from multiple patients revealed a consistent pattern of p38 subtype 17 expression in human CF, with p38- being most abundant, followed by p38- and p38-, and little or no expression of p38-β (Sinfield et al, 2013). This pattern of subtype expression is similar to that of whole heart tissue from adult humans (Lemke et al, 2001).…”
Section: Il-1 Signalling In Cfmentioning
confidence: 99%